The Impact of Home Background and Locality on the Secondary School Students’ Academic Performance in Agriculture in Enugu State, Nigeria - Ugwuoke, Cajethan Uche; Emeka Eze, Godwin; Anene Omeje, Benedicta (LPPM Undiksha, 2018)
Home background and locality are two significant factors that affect the academic performance of students in agriculture. The home determines the comfort of the students for academic activities while locality provides a conducive environment for students to study. The study was aimed at determining the impact of home background and locality on the secondary school students’ academic performance in agriculture. Survey research design was adopted. The study population was 14,750 where 1,616 respondents were selected. The sample size was made up of 624 teachers of agriculture and 992 students of agriculture from 291 secondary schools in the 17 local government areas of Enugu state, Nigeria. A structured questionnaire was used to collect data. Data collected were subjected to mean and t-test statistic to answer research questions and test the null hypotheses at 0.05 level of significance. Results show that there was the statistically significant difference in the impact of home background on the students’ academic performance in agriculture. It provides the parents with insights on the needs to make the homes conducive for learning and provide the necessary environment that would promote their children’s academic performance in agriculture.